Xanthomatous oophoritis, a rare pathology: case report with review of literature - Hota, Basanta Manjari; Bakshi, Kavitha; Movva, Naimisha; Pandirla, Swathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Xanthomatous oophoritis is a rare chronic inflammation of ovary characterized histologically with infiltration of lipid laden foamy macrophages, lymphocytes, plasma cells leading to tissue destruction. Though exact cause is not known, uterine artery embolization, gloves dusting powder and altered lipid metabolism are hypothesized to cause the pathology. A 28-year-old parous lady with history of multiple laparotomies, known case of hypothyroidism under treatment and history of adequately treated pulmonary tuberculosis was diagnosed to have right ovarian dermoid cyst, while undergoing investigation for secondary infertility. On examination she had pallor, healthy abdominal scar, and small tender fixed mass in right fornix on internal examination. She was subjected to laparotomy and right salpingo oophorectomy with left salpingectomy was performed. Histopathological examination of the resected specimen revealed to be xanthomatous oophoritis of right ovary. As this condition mimics tuberculosis and malignancy, clinical assessment, investigation and intra operative findings with the suspicion of inflammatory aetiology help to limit the extent of surgery. Hence, this case is presented for its rare occurrence as well as its need to be differentiated from other conditions like tuberculosis and malignancy of ovary.